Frontispiece: Transient Directing Groups in Metal−Organic Cooperative Catalysis. Issue 56 (7th October 2021) - Jacob, Clément; Maes, Bert U. W.; Evano, Gwilherm
Abstract : The direct functionalization of C−H bonds is among the most important transformations in organic synthesis, but its efficiency depends on its selectivity that can be controlled by the innate reactivity of the substrate or a directing group. We review and discuss in a comprehensive manner C−H functionalization processes based on the transient directing group strategy. For more information, see the Review by Gwilherm Evano et al. on page 13899 .